Diverse Papillomavirus Types Induce Endosomal Tubulation - Siddiqa, Abida; Massimi, Paola; Pim, David; Banks, Lawrence (Frontiers in Cellular and Infection Microbiology, 2019)
Previous studies have shown that the endoplasmic reticulum (ER)-anchored protein VAP is strictly required by human papillomavirus type 16 (HPV-16) for successful infectious entry. Entry appeared to be mediated in part through the induction of endosomal tubulation and subsequent transport of the virion to the trans-Golgi network (TGN). In this study, we were interested in investigating whether this mechanism of infectious entry is conserved across multiple Papillomavirus types. To do this, we analysed the role of VAP and endosomal tubulation following infection with Pseudovirions (PsVs) derived from the alpha, beta, delta, kappa and pi papillomavirus genera, reflecting viruses that are important human and animal pathogens. We demonstrate that VAP is essential for infection with all PV types analysed. Furthermore, we find that VAP and EGFR-dependent endosomal tubulation is also induced by all these different Papillomaviruses. These results indicate an evolutionarily conserved requirement for VAP-induced endocytic tubulation during Papillomavirus infectious entry.